PEMANFAATAN KEONG MAS (Pomacea canaliculata L) DAN LIMBAH CANGKANG RAJUNGAN (Portunus pelagicus) MENJADI PAKAN TERNAK UNTUK MENINGKATKAN PRODUKSI TELUR ITIK - Nurjannah Nurjannah; Subari Yanto; Patang Patang (Universitas Negeri Makassar, 2017)
The research aims to determine the effect of adding flour golden snail and flour shell crab in the feeding of ducks to increase eggs production and to improve the quality of eggshell. The Parameters observed, incluiding the production of duck’s eggs ( daily egg production, weekly egg production, egg mass) weight of duck egg (weight of eggshell and weight of the eggs content). The analysis of this thesis used variance analysis. The result of this research showed daily egg production and weekly egg production that received the best treatment lies in treatment B (awarding flour golden snail 20% and 5 % starch crab flour). Whereas the best weight of ducks egg and weight of duckshell egg is treatment D (awarding 20% flour golden snail and 10% starch crab flour)